2020
DOI: 10.3390/nu12103142
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and the Lens: New Insights into Delaying the Onset of Cataract

Abstract: Cataracts or clouding of the lens is the leading cause of blindness in the world. Age and diabetes are major risk factors, and with an increasing aging and diabetic population, the burden of cataracts will grow. Cataract surgery is an effective way to restore vision; however, alternatives to cataract surgery are required to reduce the looming cataract epidemic. Since it is well established that oxidative damage plays a major role in the etiology of cataracts, antioxidants have been promoted as therapies to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 119 publications
0
28
0
1
Order By: Relevance
“…However, there is a lack of consensus among ophthalmologists and researchers on the interest of nutritional supplements containing antioxidant vitamins, carotenoids, trace elements and/or ω3 PUFAs in ophthalmology. Dry eye disease [ 14 , 15 , 16 ], myopia complications and progression [ 72 ], cataracts [ 32 , 73 ], or sight-threatening diseases such as glaucoma, DR, and AMD [ 16 , 17 , 18 , 19 , 20 , 21 , 32 , 74 , 75 , 76 , 77 , 78 , 79 ], have been important targets of antioxidants and ω3 PUFAs. DHA is an essential structural constituent of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of consensus among ophthalmologists and researchers on the interest of nutritional supplements containing antioxidant vitamins, carotenoids, trace elements and/or ω3 PUFAs in ophthalmology. Dry eye disease [ 14 , 15 , 16 ], myopia complications and progression [ 72 ], cataracts [ 32 , 73 ], or sight-threatening diseases such as glaucoma, DR, and AMD [ 16 , 17 , 18 , 19 , 20 , 21 , 32 , 74 , 75 , 76 , 77 , 78 , 79 ], have been important targets of antioxidants and ω3 PUFAs. DHA is an essential structural constituent of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous lens proteome studies have identified putative transporters of GSH and its precursors, but not in the human lens (8,10,59). GSH uptake from extracellular suture space is putatively mediated by organic anion transporter 3 (OAT3) and sodium-dependent dicarboxylate transporter 3 (NaDC3) and efflux is mediated by multidrug resistance proteins 4 and 5 (MRP4/5) and connexins 46 and 50 (GJA3/8), which can transport molecules up to approximately 1 kDa through gap junction channels (15).…”
Section: Antioxidant Protein Networkmentioning
confidence: 99%
“…20 In contrast, results of daily supplementation with 500 mg oral vitamin C did not prevent age-related cataract changes-although mechanistically, postvitrectomy eyes may be predicted to demonstrate a greater effect, no formal controlled studies have been completed in this specific patient population to date. 21 Other methods to reduce postvitrectomy cataracts include a novel irrigation solution containing benzopyranyl esters and amides, which in a rabbit animal model prevented abnormal postvitrectomy posterior lens fiber changes. 22 Last, maintaining "face-down" positioning to reduce direct contact of the gas and the lens postsurgery has been shown to reduce postvitrectomy cataract formation after gas tamponade.…”
Section: Prevention Of Postvitrectomy Cataractsmentioning
confidence: 99%